The perceptions of general practice among Central and Eastern Europeans in the United Kingdom: A systematic scoping review. (19th January 2022) - Poppleton, Aaron; Howells, Kelly; Adeyemi, Isabel; Chew‐Graham, Carolyn; Dikomitis, Lisa; Sanders, Caroline
Abstract: Background: Around 2 million people have migrated from Central and Eastern Europe to the UK since 2004. The UK Central and Eastern European Community (UK‐CEE) are disproportionately exposed to the social determinants of poor physical and mental health. Their health and healthcare beliefs remain under‐researched, particularly regarding primary care. Objective: This review explores UK‐CEE community members' use and perceptions of UK general practice. Methods: A systematic search of nine bibliographic databases identified 2094 publications that fulfilled the search criteria. Grey literature searches identified 16 additional relevant publications. Screening by title and abstract identified 201 publications of relevance, decreasing to 65 after full‐text screening. Publications were critically appraised, with data extracted and coded. Thematic analysis using constant comparison allowed generation of higher‐order thematic constructs. Results: Full UK‐CEE national representation was achieved. Comparatively low levels of GP registration were described, with ability, desire and need to engage with GP services shaped by the interconnected nature of individual community members' cultural and sociodemographic factors. Difficulties overcoming access and in‐consultation barriers are common, with health expectations frequently unmet. Distrust and dissatisfaction with general practice often persist, promoting alternative health‐seeking approaches including transnational healthcare. Marginalized UK‐CEE community subgroups including Roma, trafficked and homeless individuals have particularly poor GP engagement and outcomes. Limited data on the impact of Brexit and COVID‐19 could be identified. Conclusions: Review findings demonstrate the need for codesigned approaches to remove barriers to engagement, culturally adapt and develop trust in GP care for UK‐CEE individuals. Community Involvement: Community members and stakeholders shaped the conceptualisation of the review question and validation of emergent themes.